Peningkatan Proses Pembelajaran Tematik Terpadu dengan Model Problem Based Learning di Kelas IV SD - Ningsih, Mai Yuli; S, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
The study in the background is that integrated thematic learning has not been appropriate. Hopefully, the aim of this study is to describe the progress of the process simultaneous thematic learning with the model problem based learning at country’s fourth grade elementary school 01 Tan Malaka Kota Padamg. His type of research is a class action study using qualitative and quantitative approaches. The subject in this study is the teacher (researches) and student of 34. Research is conducted in two cycles. The results of cycle research on RPP meeting one earn a percentage value of 81,25% (B) increasing 90,63% (SB) at meeting two and increased 94,44% (SB) on cycle two. At teacher of the cycle release one earn a percentage value of  82,14% (B) increasing 89,28% (B) at meeting two and increasing 92,85% (SB) in cycle two. Whereas at the activities of student cycle one a percentage of 78,57% (C) increased 85,71% (B) at two and increased 92,85% (SB) at the cycle two.